Study On Radioactivity In Human Teeth, Animal Bones And Soil In Selected Areas In Northern Region Of Malaysian Peninsular - Almayahi, Basim Abd Alhassen Abd Alhussein (2013)
Natural radioactivity measurements in soil, sand, and water samples obtained from Northern Peninsular Malaysia (NPM), comprising the states of Penang, Kedah, Perlis, and Perak were carried out using the Exploranium GR-135 Plus, High Purity Germanium (HPGe), and NaI (Tl) spectroscopes. The activity concentrations of 238U, 232Th, and 40K in Penang, Perlis, Kedah, and Perak states were found to be within those reported from literatures for other countries of the world. All the health hazard indices are well below their recommended value, except some soil from Kedah and Perak states. Soils with Hin and Hex< 1 are suitable for agriculture and as building materials. Also, in this study Hin and Hex< 1 for water, therefore, water after processing and filtration is safe and suitable for use in household and industrial purposes. The sites of high concentrations of displaying 226Ra/238U disequilibrium.